Security writing application of thermal decomposition assisted NaYF4:Er3+/Yb3+ upconversion phosphor. (5th June 2018) - Kumar, A; Tiwari, S P; Esteves da Silva, Joaquim C G; Kumar, K
Abstract: The authors have synthesized water-dispersible NaYF4 :Er 3+ /Yb 3+ upconversion particles via a thermal decomposition route and optimized the green upconversion emission through a concentration variation of the Yb 3+ sensitizer. The prepared particles were found to be ellipsoid in shape having an average particle dimension of 600 × 150 nm. It is observed that the sample with 18 mmol% Yb 3+ ion concentration and 2 mmol% Er 3+ ion gives optimum upconversion intensity in the green region under 980 nm excitation. Colloidal dispersibility of the sample in different solvents was checked and hexane was found to be the best medium for the prepared particles. The particle size of the sample was found to be suitable for the preparation of colloidal ink and security writing on a plain sheet of paper. This was demonstrated successfully using ink prepared in polyvinyl chloride gold medium.